Conhecendo seus direitos: uma compilação das normas garantidoras do direito a saúde - Cota, Maria do Carmo (Universidade Federal do Tocantins, 2015)
The Constitution of the Federative Republic of Brazil, 1988, outlines general guidelines for health rights and lays down rules for the regulation of health rights. Later several rules were created in order to regulate the rights established by it. Thus, in order to clarify points relating to health rights, we proceeded to an overview of legislation on health rights, starting with the Constitution of the Federative Republic of Brazil, later ace general rules on the Unified Health System and order the specific duties of each category. The survey was done with the sites of the Ministry of Health, Plateau-presidency of the Republic and others, the infra related laws, decree-laws, resolutions and decrees. The proposed objectives were to promote the raising of standards on the rights of health posts in the Constitution of the Federative Republic of Brazil in 1988, ordinary laws, decrees, resolutions and relevant Ordinances guarantees of the rights of health compiled form by category, using the method descriptive / exploratory. In the end it was concluded that laws exist and are sufficient to ensure the health of all Brazilians, however are not applied and are often not required by lack of understanding of conditions, given the amount and variety of regulatory standards, decrees, ordinances During the search, several opportunities encountered repealed laws and ordinances, where a rule repeals another, the rule repealed repealing the other and so on. So compile the guarantors of the health standards right for each category in a single document will facilitate the form of service to the person and cause them to have access to the set of actions and services necessary for the promotion, protection and recovery of their health, not to be discriminated against or suffer restriction or denial of care, actions and health services. The should have full disclosure, after approved by the Examining Committee and released by the funding institutions of the master in order to achieve its main objective which is to guarantee access to justice and the realization of human rights.